Fatal silicosis in a funeral arts’ craftsman - Calisti, Roberto; Ballatori, Gianfranco (La Medicina del Lavoro, 2016)
Background: The current scientific debate on silica and cancer has often led to overlooking the persisting risk of lung fibrosis from crystalline silica. Case report: During 2000, when 54 years old, a funeral arts’ craftsman began to suffer from persistent, hacking cough; radiography and high resolution computed tomography (HRCT) showed thin sub-pleural nodulations of the lungs, mainly in the upper fields. Two years later, increasing dyspnoea appeared and HRCT revealed vast consolidative opacities in both upper fields. Bronchial biopsies documented lung fibrosis and silicosis was diagnosed. In 2003, large amounts of crystalline silica were found in a stone used by the patient and in the dust deposited inside his workshop. In 2004 the patient abandoned his work. He died in 2008 from respiratory failure and infectious complications. Discussion: Histology is uncommonly available for the differential diagnosis of lung fibrosis so that, when imaging is not accompanied by appropriate recollection and assessment of occupational histories, new cases of silicosis may easily remain unrecognized. After some years from its onset, this fatal silicosis case showed a relatively rapid progression, that continued after exposure cessation. The disease derived from working conditions that the patient and his only colleague, both craftsmen operating in their own workshop, didn’t recognize as hazardous prior to an external intervention. Conclusions: Severe and fatal silicosis is still present in Italy, even in unusual occupational contexts. At present the disease may be more difficult to identify than in the past; collaboration between clinicians, radiologists and occupational physicians is strongly needed. Ad hoc industrial hygiene surveys give a very relevant support to diagnosis and prevention of silicosis.